(untitled) (Research, Society and Development, 2021)
Goals: Validate the educational booklet for the comfort promotion of the relatives of people in intraoperative period. Methodology: It’s a methodological study based on the "Recommendations for the Conducting and Reporting of Delphi Studies", made from October of 2019 to August of 2020, in a big public hospital in Bahia, Brazil. The study was developed in three stages: Situational diagnostic and bibliographic survey, Educational booklet development and Educational booklet validation by the experts. The evaluation happened in two moments: For the quantitative data analysis was used the concordance rate proposed by Domingues and collaborators, and for the qualitative data was used the analysis proposed by Bardin. Results: At the first moment 84,6% of the approached topics had an unsatisfactory concordance rate, under 80%. At the second round,after changes in the booklet, only one item didn’t have concordance rate of 100%. On the qualitative analysis, the booklet was considered a important tool for the comfort promotion and necessary guidance for the monitoring process, and pointing possibilities and limits for it implementation. Conclusion: The booklet was considered valid when it comes to comfort promotion to the relatives of people in intraoperative period.